DICTIONNAIRE D'HISTOIRE ET DE GEOGRAPHIE ECCLESIASTIQUES - Baudrillart, Alfred (dirección) (1912)
CONTENIDO: V. 1 AACHS-ALBUS. -- V. 2 ALCAINI-ANEURIN. -- V. 3 ANFORARIA-ARFONS. -- V. 4 ARGAIZ-ATHAULF. -- V. 5 ATHEISME-AZZON. -- V. 6 BAADER-BAVIERE. -- V. 7 BAVIERE-BENOIST.-- V. 8 BENOIT-BISCIONI. -- V. 9 BISHOP-BOUILLI. -- V. 10 BOUILLON-BZOVIUS. -- V. 11 CAABEIRO-CATULENSIS. -- V. 12 CATULINUS-CLINCHAMP. -- V. 13 CLINGE-CZORNA. -- V. 14 DABERT-EGER. -- V. 15 EGERIE-EUSEBIE. -- V. 16 EUSICE-FILLE-DIEU. -- V. 17 FILLES-FRANCAIS. -- V. 18 FRANCE-FRERES